Family-Based Health Education as an Effort to Improve Self-Care Management among Elderly with Type 2 Diabetes Mellitus Toward Sustainable Development Goal 3 - Hasifah; Wa Mina La Isa; Apriani Susmita Sari; Erna Kadrianti; Darwis; Muzakkir (Jurnal Penelitian Pendidikan IPA, 2026)
Type 2 Diabetes Mellitus (T2DM) among elderly individuals remains a major global health challenge and contributes to Sustainable Development Goal 3 (Good Health and Well-Being). Elderly patients often experience limitations in self-care management due to cognitive decline, multimorbidity, and reduced physical function. This study aimed to analyze the effectiveness of family-based health education interventions in improving self-care management among elderly patients with T2DM. A systematic literature review was conducted following the PRISMA guideline. Articles were obtained from PubMed, CINAHL, ScienceDirect, and Garuda databases published between 2019–2024. The review included quantitative studies using randomized controlled trials and quasi-experimental designs. Study quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. A total of 13 studies met the inclusion criteria. The findings showed that family-based health education significantly improved dietary adherence, medication compliance, self-monitoring of blood glucose, self-efficacy, and glycemic control, including reductions in HbA1c levels (p < 0.05). Family involvement also enhanced emotional support and continuity of care at home. In conclusion, family-based health education is effective in improving self-care management among elderly patients with T2DM.